With Whom Is Peter Eating in Antioch? Reading τὰ ἔθνη in Galatians 2:12 as Including Nonbelieving Gentiles. - Bühner, Ruben A. (Journal of Biblical Literature, 2024)
In his Letter to the Galatians, Paul says that Peter ate with τὰ ἔθνη in Antioch (2:12). In this context, the majority of commentators read the phrase τὰ ἔθνη as a reference to gentiles who believe in Christ, departing from its predominant usage in Paul's writings. However, this widespread and consequential assumption that Peter ate only with Christ-believing gentiles is not compelling. In fact, such an understanding is mainly based on prior scholarship that assumed that Jews, even in the diaspora, lived in isolated contexts and could not have eaten with non-Jews. In contrast, I argue that there are neither linguistic nor contextual reasons in Gal 2 for limiting the people with whom Peter eats to Christ-believing gentiles. Instead, historical studies suggest that the expression τὰ ἔθνη refers to Peter eating with different kinds of gentiles, which also includes non-Christ-believing gentiles at everyday occasions such as private dinner gatherings. This changes our understanding of the context of Peter's commensality as well as Peter's position itself.